A Shared Focus: Comparing the Australian, Canadian, United Kingdom and United States Pharmacy Learning Outcome Frameworks and the Global Competency Framework - Ieva Stupans; Jeffrey Atkinson; Arijana Meštrović; Rose Nash; Michael J. Rouse (MDPI AG, 2016)
This paper presents an analysis of the end of degree expectations, expressed as learning outcomes, for pharmacy graduates from Australia, Canada, United Kingdom and United States. The authors compare the end of degree expectations, through mapping these requirements to the International Pharmaceutical Federation (FIP) Global Competency Framework (GbCF). The anticipated end of degree expectations are similar but also reveal some individual characteristics. Irrespective of degree title, achievement of learning outcomes specified in any one of the four jurisdictions should enable students to become pharmacists who are patient-orientated medicines experts. The mapping provides impetus for cross-border institutional networking to generate a dependable set of assessment tools across national borders developing a common metric for outcome assessment irrespective of different program delivery.